Harm Reduction Policy, Political Economy, and Insite - Virdo, Guytano (Healthy Dialogue, 2012)
Abstract: This paper seeks to answer why Insite, Vancouver's safe injection facility, continues to be a controversial issue, given that empirical investigations of the facility have demonstrated that the site improves health and saves health care dollars. As Insite represented a shift to harm reduction policy, from historically dominant drug control policy, it has drawn opposition from local, national and international players. Using a political economy framework, this paper looks at the population around Insite, examining who the clients are and whether the facility is beneficial to them. The Downtown Eastside of Vancouver, where Insite is located, is known to be one of the poorest neighbourhoods in Canada, and as such the population is extremely marginalized (The Globe and Mail, 2008). This paper argues that the attempts by the federal Conservative Party to shut down Insite are based on ideology rather than the effectiveness of the facility. Using the Gramscian concept of hegemony, this paper argues that the federal Conservative Party attempted to use its hegemonic dominance to close down Insite. This paper will also briefly discuss the legal history of Insite, and the empirical literature, briefly summarizing the evidence researchers have found.